Respon Siswa Terhadap Penerapan Multi Metode Pembelajaran Hubungannya Dengan Prestasi Belajar Kognitif Mereka Pada Mata Pelajaran Pendidikan Agama Islam - Ririn Khairunnisa (Gunung Djati Conference Series, 2022)
The aims of this research are 1) Student responses to the application of multiple learning methods, 2) Student's cognitive learning achievement, 3) The relationship between student responses to the application of multiple learning methods and their cognitive learning achievement in Islamic religious education subjects for class VIII SMPN 2 Cielunyi. This study uses a quantitative approach and correlation method. Data collection techniques using observation, questionnaires, tests, and documentation. The technical data analysis are: partial analysis, and correlation analysis. The results of this study are: 1) realistic student responses to the application of multi-methods with a high category of 4.31 which is in the interval 3.50-4.50. 2) students' cognitive learning achievement in Islamic Religious Education subjects in the high category with an average value of 78 which is in the 70-79 interval. 3) The relationship between students' responses to the application of multiple methods with cognitive learning achievement of students in Islamic Religious Education subjects is categorized as moderate with a correlation of 0.403. Therefore there is a relationship between response students to the application of multiple learning methods with their cognitive learning achievement in Islamic education subjects.